Eye Position Based Wheel Chair Control for Physically Challenged - Darwin, R (International Journal of Computer Sciences and Engineering, 2025)
A powered wheel chair is a mobility-aided device for persons with moderate/severe physical disabilities or chronic diseases as well as the elderly. In order to take care for different disabilities, various kinds of interfaces have been developed for powered wheelchair control such as joystick control, head control and sip-puff control. Many people with disabilities do not have the ability to control powered wheel chair using the above mentioned interfaces. The proposed model is a possible alternative. In this project, we have considered mainly the patients with the problem of Quadriplegia. These patients have paralysis below neck region. In this, we use the optical-type eye tracking system to control powered wheel chair. User‘s eye movement are given as input in the form of a image to MATLAB software. When user looks at appropriate angle, software will provide command based on the angle of position of pupil i.e., when user moves his eyes balls, left (move left), right (move right), up (move forward) and down (stop or reverse). In all other cases wheel chair will proceed straight. Once the image has been processed it moves onto the second part, Arduino. These will take the output from the laptop via a Bluetooth device and convert the signal into command signals that will be sent to the wheelchair motor circuit for movement. This project mainly focuses on wheel chair that process based on the movement of the eye. Adding to this, the wheel chair can also be used to people who has finger movements by using the touch control via mobile.